HIV influences clustering and intracellular replication of hepatitis C virus. Issue 2 (24th November 2020) - Goyal, Ashish; Perelson, Alan S.; Kandathil, Abraham J.; Quinn, Jeffrey; Balagopal, Ashwin; Ribeiro, Ruy M.
Abstract: HCV and HIV coinfection is common and HIV leads to increased HCV viraemia and accelerated disease progression. However, the biological basis of this interaction remains poorly understood and little is known about the impact of HIV on HCV replication at the cellular level. We analysed HCV RNA, based on single‐cell laser‐capture microdissection, in liver biopsies from monoinfected (n = 4) and HCV/HIV‐coinfected (n = 5) participants. HCV RNA was assayed in 3200 hepatocytes with information of spatial position. We compared HCV RNA levels and clustering properties of infection between mono‐ and coinfected participants, and developed a mathematical model of infection. Although the median plasma HCV RNA level and the fraction of infected cells were comparable in monoinfected (7.0 log10 IU/mL and 30%) and coinfected (7.3 log10 IU/mL and 40%) participants, the median HCV RNA per infected hepatocyte in monoinfected (2.8IU) was significantly lower than in coinfected (8.2IU) participants ( p = .03). Clustering of infected cells was more prominent in monoinfected participants (91% of samples) than in coinfected participants ( 48%), p = .0045, suggesting that spatial spread may be influenced by HIV coinfection. Interestingly, when clustering does occur, the size of clusters is similar in both types of infection. A mathematical model of infection suggested that HIV allows higher intracellular accumulation of HCV RNA by impeding the export of HCV RNA. Our observations show that HIV coinfection impacts intracellular accumulation of HCV RNA and the clustering of HCV‐infected cells, but to a less extent the fraction of HCV‐infected cells.